Iles-iles (Amorphophallus muelleri Blume); description and other characteristics - SUMARWOTO SUMARWOTO (Biodiversitas Journal of Biological Diversity, 2005)
The aims of the research was to asses describe and find out the others iles-iles (Amorphophallus muelleri Blume) properties on the vegetative growth and age until reach the generative growth. The research was conducted at the experimental fields of Bogor Agricultural University, Darmaga from November, 1999 to May, 2003 and at the experimental field of the Agricultural Technology Assesment Installation Unit, Sukabumi from February 2001 to April, 2002. It was found that iles-iles showed positive responses to shading, good drainage, and application of high manure (organic matter).The phenological study gave additional information on describing this species and also on cultivation aspects such us: planting distance, planting depth, the best time of harvest, and concentration of tuber andbulbil glucomannan.@2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: Amorphophallus muelleri Blume, description, glucomannan, tuber, bulbil